DEVELOPING ARTS APPRECIATION IN THE PANDEMIC: STUDENTS EXPERIENCES OF ONLINE ARTS COLLABORATION - Althien John Pesurnay; Winta A. Guspara (Universitas Pendidikan Ganesha, 2021)
Arts and arts practices have been affected by the constraints of the global COVID-19 pandemic. Arts learning and teaching activities in the subject of art appreciation in Duta Wacana Christian universities have also been disrupted, necessitating online collaboration. There are not many studies being done that evaluationg arts learning and teaching during pandemics. Therefore this research is playing the role to contribute to the issue. This research spesifically focus to evaluate the learning and teaching method and also the concepts connected to arts practice in general and in the contextual arts learning and teaching activities in university setting. This result shows that during a situation where in-person classroom instruction is not possible, students were still succesfull increasing their appreciation of arts. Students were engaged by collaborative art projects where they had to develop a concept and produce a digital product to be shared and critiqued in an online forum. Data from a post-project mixed method survey, students indicated that this process of developing digital products enhanced their appreciation of arts. This project demonstrates that online collaborations in the arts assists in the development of forms of art appreciation in students from a variety of majors. Arts collaboration can be done via online technology by non-arts students. These types of collaborations are useful in encouraging students to adapt academically and artistically